An investigation into the effect of electric field on the performance of Dielectric Barrier Discharge plasma actuators - Cheong, M.; Greig, A.; Gibson, Brad; Arjomandi, M. (Elsevier Science Inc., 2011)
The influence of the inter-electrode electric field of a single Dielectric Barrier Discharge (DBD) actuator on the performance of the device was investigated. The electric field of the actuator was manipulated through the variation of the angle between the electrodes of the actuators. Response forces generated by the plasma actuators were used as performance indicators for these devices. These forces were measured directly utilizing a highly sensitive balance scale. It was verified that depending on the orientation of the variation of the angle between the electrodes, the performance of the actuator may be decreased or increased when compared to a DBD on a flat dielectric plate more commonly investigated in literature. The manner in which the ionic wind flows over the actuators was also explored in the effort to elucidate the influence of the variation of the angle between the electrodes on the response force generated by the device. Results demonstrated that the response forces generated by the actuators may be improved by up to 50% compared to the actuator configuration on a flat dielectric plate commonly investigated. These results indicate the potential available to advance plasma technology by physically manipulating these devices to increase the performances of the actuators.